Lewy body dementia – A case report (Journal of Psychiatrists' Association of Nepal, 2024)
Lewy body dementia (DLB) is a form of cognitive impairment in ages over 65 years. Early diagnosis of DLB has been challenging ; particularly in the context of differentiation with Parkinson’s disease dementia and other forms of dementia, such as Alzheimer’s disease and rapidly progressive dementia. Clinically the distinction is important because it can have implications for management and prognosis.